The transversely split gracilis twin free flaps - Divya N. Upadhyaya; Vaibhav Khanna; Surajit Bhattacharya; Sandeep Garg; Romesh Kohli (Indian Journal of Plastic Surgery)
The gracilis muscle is a Class II muscle that is often used in free tissue transfer. The muscle has multiple secondary pedicles, of which the first one is the most consistent in terms of position and calibre. Each pedicle can support a segment of the muscle thus yielding multiple small flaps from a single, long muscle. Although it has often been split longitudinally along the fascicles of its nerve for functional transfer, it has rarely been split transversely to yield multiple muscle flaps that can be used to cover multiple wounds in one patient without subjecting him/her to the morbidity of multiple donor areas.